Anti-Windup Compensator Design For Improved Tracking Performance Of Differential Drive Mobile Robot - Chan, Sing Yew (2017)
Wheeled mobile robots (WMRs) have been widely used for navigation purposes as well as industrial applications such as path tracking and obstacle detections. Differential drive robot (DDR) is one type of WMRs with a specific wheel configuration where two fixed wheels are controlled by the motors and a castor wheel is added to mechanically support its translational and rotational movements. For tracking purposes, the controller plays a very important role to ensure it does not deviate far from the targeted locations or path. In this project, a DDR is built with two DC motors. As most motors exhibit nonlinear behavior, they are modeled as a multivariable Hammerstein-Wiener structure which contains static nonlinearities and a linear system in series with each other. The identification of the linear model is performed via time response analysis with different types of inputs, whereas the nonlinearities are estimated via several tests in MATLAB Simulink. This work also focuses on both dynamic and kinematic models of the DDR where a proportional-integral (PI) controller is designed to achieve the desired specifications in the linear region. In order to account for the nonlinear effects from the DC motor model which is mainly influenced by its bounded velocity capability, a static anti-windup compensator (AWC) is implemented which is activated when the controller output exceeds the bound. Via this strategy, a significant improvement on the tracking performance of the DDR can be observed via simulations especially when the desired path involves sharp corners or turns. 1